تأثير تمرينات تنافسية فردية و جماعية في تطوير السرعة الحركية للمناولة للاعبي المدارس الكروية بأعمار (13) سنة بكرة القدم - Nagi, Deyaa; Jwad, Haithem (Journal of Physical Education, 2015)
Football is one of the games that require accuracy and speed in performance. The aim of this current study is to develop a training curriculum for the development of the movement speed of the handling of football players for the football schools in Iraq as well as to know the impact of individual and collective competitive exercise in the development of technically gifted side presented by the movement-handling speed. The experimental method was applied on a sample of football schools ages (13 years) and for the number of (20) players which were divided into two groups. The research conclusion shows that the training curriculum which was developed by the researcher may impact positively on the results of the post tests of the experimental group